KEBIASAAN POLA KONSUMSI PADA KEJADIAN HIPERTENSI PADA USIA DEWASA DI KLINIK MITRA SEHAT - Hasan Nidlom; Eko Budi Santoso (Journal of Innovation Research and Knowledge, 2025)
Hypertension is the leading cause of death by the occurrence of stroke, myocardial infarction and kidney malfunction. Risk factors associated with hypertension can not be controlled such as genetics, age, gender, and race. While the risk factors that can be controlled as environmental factors such as behavior or lifestyle such as obesity, inactivity, stress and consumption of food. Aim. This study was to determine the relationship of diet to hypertension in adulthood in Puskesmas Keputih Surabaya. Methods of using analytic observational research with cross sectional design. The population in this study were all patients of hypertension with a sample of 62 people. The sampling technique used purposive sampling technique. Collecting data using questionnaires and observation. Data analysis using chi-square test. The results showed that dietary patterns in Puskesmas Keputih Surabaya largely balanced as much as 40 respondents (64.5%) and a small balanced as much as 22 respondents (35.5%). Hypertension in Puskesmas Keputih most of stage 1 as many as 38 respondents (61.3%) and a small stage 3 by 5 respondents (8.1%). The results of chi-square analysis P = 0.002. Conclusion There is a correlation study of dietary patterns with hypertension in adulthood in Puskesmas Keputih Surabaya. Expected in hypertensive patients to maintain a diet in order to keep blood pressure within normal limits